Coping Strategies, Stress Levels of Housewives, and Their Influence on Family Communication - Lidiawati; Krisnatuti, Diah; Defina (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2025)
Family communication is essential for family life. This study aimed to determine the influence of family characteristics, coping strategies, and homemaker stress levels on family communication. The respondents in this study were housewives with children of a minimum age of junior high school. A total of 100 respondents were obtained using volunteer sampling techniques, of which 50 people were domiciled in villages and 50 in cities in the Bogor area. The results indicate that the education of husbands and wives and family income in villages are lower than those in cities. However, the number of children living in cities was more significant than that living in villages. In addition, the number of mothers in villages categorized as high was more significant than in cities. Likewise, regarding stress levels, the average stress level of mothers in villages was lower than that of mothers in cities. The average communication of mothers in villages and cities was higher for conversation-oriented communication than conformity. The results of the regression test showed that stress levels and coping strategies had a significant positive effect on family communication during conversations. In addition, coping strategies significantly positively affected communication orientation conformity. This implies that stress and coping strategies influence family communication. Thus, family conformity orientation communication must continue to improve to reduce maternal stress levels.